2009
DOI: 10.1038/ijir.2008.66
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial aspects of sexual recovery after prostate cancer treatment

Abstract: Prostate cancer affects one in six American men. Erectile and sexual dysfunctions are long-term side effects of prostate cancer treatment. PubMed database was searched for papers on prostate cancer-related sexual recovery for men and couples. The search yielded articles on (1) the treatment of erectile dysfunction, (2) men's psychological and culturally diverse adaptation to the sexual side effects; (3) the impact of prostate cancer on couples' relationships; and (4) interventions to promote sexual function. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 75 publications
2
45
0
2
Order By: Relevance
“…74 Recently, review articles discussing the side effects of androgen ablation therapy have stated that this treatment also impacts cognitive functioning. 75 HRQOL is not only synonymous with health status but also encompasses the reactions to coping with life circumstances, in this case cancer (living with it, living after surviving or coming to terms with cancer). The QOL of a patient will be determined by the mental and physical status before diagnosis, attitude toward your disease, willingness to make compromises, undergo therapy and take advantage of every supportive care service that will help reduce stress and increase coping skills, the stage of disease at the time of diagnosis.…”
Section: Psychological Issues In Prostate Cancer Related To Developmementioning
confidence: 99%
“…74 Recently, review articles discussing the side effects of androgen ablation therapy have stated that this treatment also impacts cognitive functioning. 75 HRQOL is not only synonymous with health status but also encompasses the reactions to coping with life circumstances, in this case cancer (living with it, living after surviving or coming to terms with cancer). The QOL of a patient will be determined by the mental and physical status before diagnosis, attitude toward your disease, willingness to make compromises, undergo therapy and take advantage of every supportive care service that will help reduce stress and increase coping skills, the stage of disease at the time of diagnosis.…”
Section: Psychological Issues In Prostate Cancer Related To Developmementioning
confidence: 99%
“…Radical curative treatments can result in nerve or tissue damage, either eradicating erections or taking up to two years for partial erections to be recovered [20] and hormonal treatments can result in side effects that might be experienced as challenging to masculinity (e.g. loss of libido and gynecomastia).…”
Section: Introductionmentioning
confidence: 99%
“…[69][70][71][72] This may not reliably occur at this time, particularly for gay men, 73 African Americans 70 and other ethnic groups. 74 As the side effects of prostate cancer surgery are quite dramatic, uninformed patients would be more susceptible to regretting their treatment choice. Davison et al 64 studied treatment regret in prostate cancer and found that only a very small percentage of men (4%, N ¼ 140) regretted having decided on surgical treatment despite significant sexual side effects.…”
Section: Penile Rehabilitationmentioning
confidence: 99%